2018
DOI: 10.3389/fimmu.2018.00793
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Evidence for a Direct Interaction of Progranulin and Tumor Necrosis Factor Receptor-1 and Tumor Necrosis Factor Receptor-2 From Cellular Binding Studies

Abstract: Progranulin (PGRN) is a secreted anti-inflammatory protein which can be processed by neutrophil proteases to various granulins. It has been reported that at least a significant portion of the anti-inflammatory effects of PGRN is due to direct high affinity binding to tumor necrosis factor receptor-1 (TNFR1) and TNFR2 and inhibition of tumor necrosis factor (TNF)-induced TNFR1/2 signaling. Two studies failed to reproduce the interaction of TNFR1 and TNFR2 with PGRN, but follow up reports speculated that this wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 34 publications
0
11
1
Order By: Relevance
“…Although the exact role of TNFRs is not yet understood, soluble TNFRs may function as decoys for TNFa (36). In the present study, serum PGRN concentrations were correlated mildly with TNFR1 concentrations; however, it should be noted that other research groups have not found any direct physical or functional interaction between PGRN and TNFRs (37,38).…”
Section: Discussioncontrasting
confidence: 66%
“…Although the exact role of TNFRs is not yet understood, soluble TNFRs may function as decoys for TNFa (36). In the present study, serum PGRN concentrations were correlated mildly with TNFR1 concentrations; however, it should be noted that other research groups have not found any direct physical or functional interaction between PGRN and TNFRs (37,38).…”
Section: Discussioncontrasting
confidence: 66%
“…Certain studies concluded that the central mechanism of inhibiting inflammation was the binding and antagonism by PGRN of the tumor necrosis factor receptor (TNFR)-1 and TNFR-2 [95,96], thus blocking the action of the proinflammatory cytokine tumor necrosis factor (TNF-α). However, other studies have not replicated these findings [97,98]; this issue is still unresolved [99]. It has been shown that PGRN can block the downstream activity of TNF-α by inhibiting the expression and release of CXCL9, CXCL10 or IL-10 [58,100].…”
Section: Involvement Of Pgrn In Disease Processesmentioning
confidence: 99%
“…Progranulin binds to TNFR1 and TNFR2 on immune cells, mostly macrophages and Tregs, competing with TNF-alpha for receptor binding, thereby inhibiting TNF-alpha pro-inflammatory activity [ 7 ]. It is important to mention to that progranulin interaction with TNFRs remains controversial, since other groups failed to confirm a direct binding of progranulin to TNFRs [ 61 , 62 , 63 ]. These discrepancies might be due to technical differences in the surface plasmon resonance (SPR) experimental approaches used by different groups [ 64 ].…”
Section: Progranulin Binding Proteinsmentioning
confidence: 99%